Estudio geológico y plan de seguridad minera, en el área bomba de Pacchapamba unificada, empresa minera EXCELMORO S.A. cantón Portovelo provincia de El Oro. - Escobar Pardo, José Antonio (2010)
The geologic studies are constituted as the main tool in the exploration activities and exploitation of mineral locations, these they are supplemented with a group of technical norms that you/they allow the sustainable recovery of the resource and to safeguard the physical and social integrity of those who participate in this type of projects; it is for that reason that in this work it is detailed the geologic "Study and Plan of Mining Security in the Area Bomb of Unified Pacchapamba, Mining Company EXCELMORO S.A". The present project consists of nine articles, which look for to detail the geologic-structural characteristics in those that the mining activities are developed, as well as the followed processes to improve the conditions of security in the labor atmosphere. The article one and two refer to general aspects as introduction, objectives and a summary bibliographical base that he/she allows to interpret with more easiness that described in this project. The article three indicate us the field materials and of desk with their respective method and methodology applied for the development of the project. The article four are since the most important it contains a general description of the study area initially, to more it details the topographical and geologic conditions so much superficial as underground on those that the company carries out the exploration activities and exploitation of auriferous minerals. In this article it is also described the mineralogical characteristics of the existent veins and their method of exploitation. As well as aspects referred to the identification and evaluation of labor risks is related, with their respective Plans like: of Security and Industrial Hygiene, of Contingency, of Compensation and Monitored that should be used in the exploration processes, exploitation, Treatment and Benefit of Minerals for the Development of Mining Activities in the Company EXCELMORO S.A. The articles of the five at the nine refer to the discussion of the Project, conclusions and recommendations, the used bibliography and the respective annexes.